(untitled) (Wudil Journal of Science and Technology Education, 2025)
Agelanthusdodoneifolius (Loranthaceae), a hemi-parasitic plant widely used in Northern Nigerian ethnomedicine for treating malaria, wounds, and infections, was investigated for its phytochemical composition and in vitro bioactivities to validate its traditional uses. Aqueous, chloroform, and ethanol leaf extracts were subjected to qualitative phytochemical screening, revealing the presence of tannins, glycosides, saponins, phenols, and flavonoids, but the absence of alkaloids, anthraquinones, and phlobatannins. In vitro antimalarial activity against Plasmodium falciparum (5% parasitemia) was assessed using the Giemsa staining method, with chloroform and ethanol extracts exhibiting dose-dependent activity. The chloroform extract achieved 84.7% parasite elimination at 10 mg/mL after 48 hours, significantly higher than the ethanol extract (82.4%, p = 0.0145), though less potent than artemether (92.7%). Antimicrobial activity was evaluated via the broth microdilution method against Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), and Candida albicans (ATCC 10231), with minimum inhibitory concentrations ranging from 0.625 to 5 mg/mL for ethanol extracts and 1.25 to 10 mg/mL for chloroform extracts, supporting traditional uses for wound healing. Antioxidant activity, assessed by the DPPH assay, showed IC₅₀ values of 0.45 ± 0.03 mg/mL (ethanol) and 0.82 ± 0.05 mg/mL (chloroform), indicating significant radical scavenging potential compared to ascorbic acid (0.02 ± 0.01 mg/mL). These findings validate the ethnomedicinal applications of A. dodoneifolius and highlight its potential as a source of antimalarial, antimicrobial, and antioxidant agents. Further studies are warranted to isolate bioactive compounds, elucidate mechanisms of action, and assess in vivo efficacy and ecological sustainability for therapeutic development.